Energy fluxes and vertical heat transfer in the Southern Baltic Sea - Rak, Daniel; Przyborska, Anna; Bulczak, Anna I.; Dzierzbicka-Głowacka, Lidia (Frontiers in Marine Science, 2024)
This article delves into the complex dynamics of thermal energy exchange in the Southern Baltic Sea, emphasizing energy fluxes, temperature variability, and the water column's structure. It leverages observations of solar thermal energy, especially highlighting the peak of the Top Net Short-Wave Radiation in June, to scrutinize the subsequent distribution of energy and its warming impact on the marine environment. The redistribution of this energy within the environment is noticeable, with the peak of the Vertical Integral of Total Energy (VITE) occurring in late July, markedly influencing the surface layer of the Southern Baltic Sea. Furthermore, the research accentuates the Southern Baltic's function as a net energy sink, with a positive average energy budget of 5.48 W m-2, underscoring the sea's ability to absorb and redistribute solar energy and showcasing a distinctive pattern of energy absorption and emission throughout the year. Additionally, the article examines the structure of the water column, highlighting how vertical thermal energy transport is intimately linked with density differences in the water. The presence of a dicothermal layer, with its upper limit marked by the thermocline, signifies the initial decline in the quality of curve fitting to the measured values and slowing down the signal propagation, while the halocline marks the second decline. Below the halocline, the correlation significantly drops, indicating a diminished connection between deeper water temperatures and surface conditions. The article also notes a decreasing correlation in thermocline dynamics, attributed to the thermocline's deepening and changes in the Upper Mixed Layer (UML), suggesting profound alterations in vertical thermal interactions.